Enhancement of anti-corrosion and mechanical properties of alkyd-based protective paints for steel petroleum structures incorporating natural limonite pigment. Issue 1 (1st January 2018) - Abdou, M.I.; El-Sayed Ahmed, Hany; Wahab Gaber, M.A.; Fadl, A.M.
Abstract: In the present approach, natural limonite iron oxide samples from Baharyia Oasis areas have been collected and ground to the micro-sized scale to be used as pigment for upholding the corrosion resistance behavior and mechanical performance properties of protective paints for steel petroleum structures. The assessment procedure includes measuring of specific gravity, moisture content, oil absorption, particle size distribution, particle shape, pH value, soluble in water, hardness, powder color and chemical composition by XRF analysis of limonite pigment particles. X-ray diffraction (XRD) analysis was implemented to assure the phase identification of the crystalline limonite pigment particles. Dynamic light scattering (DLS) measurements were accomplished to measure the particle size distribution and Zeta-potential of these particles in suspension. Amorphous and lamellar morphology of limonite particles was manifested by scanning electron microscopy (SEM) micrographs. EDX investigation was employed to give a semi-quantitative analysis and the chemical composition of limonite pigment. Different alkyd-based coating formulations were modified using various uniformly dispersing amounts of the processed limonite pigment particles as bi-functional modifier. The anti-corrosion performance properties of the considered limonite modified coating formulations against unmodified blank coating were studied by accelerated corrosion experiment (salt spray chamber) after 500 h exposure in 5% NaCl solution. The obtained results revealed a significant improvement in the rust grade, blistering size, color tolerance and adhesion performance of limonite modified coated steel films compared to unmodified conventional coating. To confirm the previous concept, weight loss method was performed. The mechanical performance properties for these films were investigated by adhesion cross-cut, bend and impact coating tests to confirm their application efficiency. From the recorded data it was found that, the adhesion properties, elongation character and resistance to rapid deformation of these coatings increased significantly to the steel surface with increasing the limonite pigment (%) by weight in the coating formulation. The results obtained compared with the ASTM and paint handbooks and found satisfactory for producing color paint pigment.